TUTURAN TINDAK PELANGGARAN DALAM RETORIKA POLISI LALU LINTAS DI KOTA PAMEKASAN - Oktasari, Anisa Fajriana; Amalia, Laili; Anjarani, Devie Restia (Kantor Bahasa Banten, 2018)
This rhetoric is defined as the art of speaking well, used in the communication process.The research on the linguistic analysis of languages and includes rhetoric. The modern rhetoric includes a powerful memory, power and high-fantasy creations, the proper disclosure of techniques and the power of proof as well as a proper assessment.Berretorika should also be accountable accompanied word choice and tone that suits the purpose, space, time, situation and who're talking that faced.This descriptive qualitative research methods and use interview techniques. The purpose of this research was conducted to describe the way the traffic police in the town of Pamekasan composing words as effectively in business speak.Based on the results of the analysis, the researchers concluded that the wording and ideas delivered Polantas Pamekasan at the time of operation is in compliance with traffic the way a good greeting to motorists who violate the traffic.The way that they do among other things asks politely and firmly crack down on offense, and give, let the community know what alleges that in constrained, so it doesn't need fixing.